Im pretty sure the answer is 20
Answer:
4+3x
It's pretty straight forward, you have the number 4 that is added to the rest of the expression because sum is addition, and the product of 2 numbers is multiplication so it would make 3(x) or 3x, which results in 4+3x.
The present age of Jane is 45 years old and present age of her sister is 9 years old
<em><u>Solution:</u></em>
Let the present age of Jane be "x"
Let the present age of her sister be "y"
<em><u>Jane is 5 times older than her sister</u></em>
present age of Jane = 5(present age of her sister)
x = 5y ---------- eqn 1
<em><u>In 3 years, Jane’s sister will be 1/4 her age</u></em>
Age of sister after 3 years = 3 + y
Age of jane after 3 years = 3 + x
Age of sister after 3 years = 1/4(age of jane after 3 years)
Substitute eqn 1 in above equation
Substitute y = 9 in eqn 1
x = 5(9)
x = 45
Thus present age of Jane is 45 years old and present age of her sister is 9 years old
E = 3(6^2)
E = 3(36)
And your answer is E = 108 :)